Penerapan model kooperatif tipe think pair share untuk meningkatkan minat dan hasil belajar siswa di SMP PGRI Mumbulsari - Afifah, Ully; Nurjanah, Umi; Bukhori, Imam (JURNAL BIOSHELL, 2023)
ABSTRACT This study aims to increase student interest and learning outcomes with a think pair share cooperative model at SMP PGRI Mumbulsari, the type of research used is classroom action research (CAR). Based on the results data, it is known that the percentage of classical completeness in the pre-cycle is 25.80% of the 31 students who did not complete and 8 students who did not complete, in the first cycle 54.83% of the 31 students there were 14 students who did not complete and 17 students who completed because the students were less focused when the researcher explained the material, many of the students did not pay attention to it because other class conditions were not conducive, another cause the students were still confused when the researcher directed the students to carry out learning by using the Think Pair Share type cooperative model and in the second cycle occurred the increase in the value of completeness that is 87.09% of 31 students only 4 students who did not complete and 27 students completed. And the interest result data is known to be the percentage in the pre-cycle, which is 64.18, an increase after the research is 89.95. Thus, it can be concluded that the application of the TPS type cooperative model can increase the interest and learning outcomes of students of SMP PGRI Mumbulsari. Keywords: student interest, learning outcomes, think pair share cooperative learning model. ABSTRACTThis study aims to increase student interest and learning outcomes with a think pair share cooperative model at SMP PGRI Mumbulsari, the type of research used is classroom action research (CAR). Based on the results data, it is known that the percentage of classical completeness in the pre-cycle is 25.80% of the 31 students who did not complete and 8 students who did not complete, in the first cycle 54.83% of the 31 students there were 14 students who did not complete and 17 students who completed because the students were less focused when the researcher explained the material, many of the students did not pay attention to it because other class conditions were not conducive, another cause the students were still confused when the researcher directed the students to carry out learning by using the Think Pair Share type cooperative model and in the second cycle occurred the increase in the value of completeness that is 87.09% of 31 students only 4 students who did not complete and 27 students completed. And the interest result data is known to be the percentage in the pre-cycle, which is 64.18, an increase after the research is 89.95. Thus, it can be concluded that the application of the TPS type cooperative model can increase the interest and learning outcomes of students of SMP PGRI Mumbulsari. Keywords: student interest, learning outcomes, think pair share cooperative learning model.